Tes sitotoksisitas bahan kalsium hidroksida dengan menggunakan kultur sel fibroblast embbio ayam kampung (Gallus domesticus) in vitro=Evaluation of the Cytotaxicity Effects of Calcium Hidroxide on Gallus domesticus Embry - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
The purpose of the present investigation was to study the cytotoxicity effect of calcium hydroxide in fibroblast cell culture system. Thirty plates of monolayer culteres of an established embrionic fibroblast cell of Gallus domesticus were used in this medium was decanted Filter paper disc were sluraled with calcium hydroxide in various concentration (1 persen, 3 persen, 6 persen, and 7 persen) and placed on the agar overlay and 1 filler paper disc was saturated- with steril aquadest as a control. The plates were returned to the incubator for 24 hours (15 plates) and 48 hours (15 plates). The agar was decanted and the monolayer was fixed in 10 persen formalin and stained with methyleen blue and the diameters of the zone of cell death were recorded. All four of the calcium hydroxide in various concentration produced cell death when filler paper disc were placed on the agar overlay. There were no zone of cell death around any of the control disc. This study indicates that there are significance differences between the four experimental groups and there is a significance positive corellation between the calcium hydroxide concentration and zone of cell death. After 48 hours the cytotoxicity effect of calcium hydroxide was decreased.